Effect of a forensic nursing virtual education course on knowledge and clinical decision-making of master’s nursing students in Iran: a non-equivalent control group pre- and post-test study - Zeynab Firuzi; Mitra Sedghi Sabet; Fateme Jafaraghaee; Hedayat Jafari; Ehsan Kazemnezhad Leyli; Samad Karkhah; Mohammad Javad Ghazanfari (Journal of Educational Evaluation for Health Professions, 2022)
Purpose Forensic nursing is a specialty in the nursing profession based on legal procedures. This study aimed to assess the effect of a forensic nursing virtual education course on knowledge and clinical decision-making among master’s nursing students. Methods In a quasi-experimental study with a pre- and post-test, 106 master’s nursing students at Guilan (n=65) and Mazandaran (n=41) Universities of Medical Sciences, Iran were enrolled. Data were collected using census sampling from March to April 2021. Participants in the intervention group received a forensic nursing virtual education course in three 90-minute sessions for 2 days. Results A total of 88 out of 106 master’s nursing students were enrolled in this study. The mean post-education score for knowledge in the intervention group was significantly higher than in the control group (12.52 vs. 7.67, P<0.001). The mean post-education score for clinical decision-making in the intervention group was significantly higher than in the control group (16.96 vs. 13.64, P<0.001). Conclusion The level of knowledge and clinical decision-making of master’s nursing students regarding forensic evidence improved after the forensic nursing virtual education course in the intervention group compared to the control group. Nursing managers and policymakers can develop appropriate strategies to improve the knowledge and clinical decision-making of nursing students by using forensic nursing education courses in the curricula of nursing programs, especially in postgraduate education as an elective or mandatory course.